2017
DOI: 10.1002/maco.201709880
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cavitation erosion resistance of copper alloy in different liquid media

Abstract: To evaluate the influence of liquid property on cavitation erosion resistance of the copper alloy, an experimental investigation is performed with the ultrasonic vibratory apparatus. Liquid media of deionized water, tap water, and 3.5 wt.% NaCl solution are selected. The cumulative mass loss rate and microhardness are measured and surface morphology observed at different erosion time. The results show that the cumulative mass loss increases consistently with the erosion time, and the highest cumulative mass lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…With distinct twin-phase structures, the copper alloy bears explicit cavitation erosion characteristics. 30 The results shown in Figure 7 well demonstrate the development of cavitation erosion on the surfaces of the copper alloy specimens. At T = 15 min, small sparsely distributed needle-like erosion pits are witnessed, signifying non-severe cavitation erosion, as shown in Figure 7(a).…”
Section: Resultsmentioning
confidence: 57%
“…With distinct twin-phase structures, the copper alloy bears explicit cavitation erosion characteristics. 30 The results shown in Figure 7 well demonstrate the development of cavitation erosion on the surfaces of the copper alloy specimens. At T = 15 min, small sparsely distributed needle-like erosion pits are witnessed, signifying non-severe cavitation erosion, as shown in Figure 7(a).…”
Section: Resultsmentioning
confidence: 57%
“…Although FeCrNiBSiMo x ( x = 1.5) specimen had the best cavitation erosion resistance in the four as‐deposited specimens, the microhardness of FeCrNiBSiMo x ( x = 1.5) specimen in the four as‐deposited specimens was not the highest. This phenomenon indicated that microhardness was not the only factor affecting the cavitation erosion resistance of the as‐deposited specimens …”
Section: Resultsmentioning
confidence: 97%
“…26 It has been demonstrated that the fatigue strength of various materials such as aluminum alloys, copper alloys, and stainless steel is improved with the application of the ultrasonic cavitation technique. [27][28][29][30][31] However, treating Mn-Cu alloy with ultrasonic cavitation has rarely been reported heretofore.…”
Section: Introductionmentioning
confidence: 99%